2022
DOI: 10.3390/v14091966
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Spike and Nucleocapsid Antibody Response in Vaccinated Croatian Healthcare Workers and Infected Hospitalized Patients: A Single Center Cohort Study

Abstract: Studies assessing the dynamics and duration of antibody responses following SARS-CoV-2 infection or vaccination are an invaluable tool for vaccination schedule planning, assessment of risk groups and management of pandemics. In this study, we developed and employed ELISA assays to analyze the humoral responses to Nucleocapsid and Spike proteins in vaccinated health-care workers (HCW) and critically ill COVID-19 patients. Sera of more than 1000 HCWs and critically ill patients from the Clinical Hospital Center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 99 publications
1
4
0
Order By: Relevance
“…We did not detect any sex differences, contrasting with other studies that found higher SARS-CoV-2 anti-spike IgG antibody levels in females compared to males 20,21,24,25 . However, similar to our findings, Brlić P. et al reported no significant gender-related differences in post-vaccination antibody levels among a cohort of 1072 healthcare workers in Croatia 26 . The lack of consistency regarding the association of biological sex and COVID-19 vaccine-induced humoral responses warrants further evaluation.…”
Section: Discussionsupporting
confidence: 90%
“…We did not detect any sex differences, contrasting with other studies that found higher SARS-CoV-2 anti-spike IgG antibody levels in females compared to males 20,21,24,25 . However, similar to our findings, Brlić P. et al reported no significant gender-related differences in post-vaccination antibody levels among a cohort of 1072 healthcare workers in Croatia 26 . The lack of consistency regarding the association of biological sex and COVID-19 vaccine-induced humoral responses warrants further evaluation.…”
Section: Discussionsupporting
confidence: 90%
“…The antibody concentration levels increased over time for both groups. Even though there is not much literature comparing symptomatic and asymptomatic patients, higher anti-nucleocapsid was detected in critically ill patients with COVID-19 as compared with non-critically ill [31]. In another study in the Netherlands [32], higher anti-nucleocapsid antibodies were detected in moderate or severe cases while undetectable in asymptomatic patients.…”
Section: Discussionmentioning
confidence: 96%
“…This is supported by high levels of SARS-CoV-2 spike protein IgG antibodies, consistent with vaccine immunization versus slightly positive IgG anti-nucleocapsid antibodies, possibly due to an early prior infection, even though no known exposure was available to inform the timing of the infection. Although anti-nucleocapsid antibodies are indicative of past or recent SARS-CoV-2 infection, anti-spike protein antibodies can be induced either by SARS-CoV-2 infection or COVID-19 vaccination [ 16 , 17 ]. In our case, the vaccination was only three weeks before, and, moreover, the level of anti-nucleocapsid antibodies was slightly positive, but dropped after a week.…”
Section: Discussionmentioning
confidence: 99%